Derrida : Ethics Under Erasure. - Anderson, Nicole (Continuum studies in continental philosophy., 2012)
Derrida's work is controversial, it's interpretation hotly contested. Derrida and an Ethics in Practice offers a new way of thinking about ethics from a Derridean perspective, linking the most abstract theoretical implications of his writing on deconstruction and on justice and responsibility to representations of the practice of ethical paradoxes in everyday life. The book presents the development of Derrida's thinking on ethics by demonstrating that the ethical was a focus of Derrida's work at every stage of his career. In connecting Derrida's earlier work on language with the ethics implica.